2017
DOI: 10.1371/journal.pone.0179694
|View full text |Cite
|
Sign up to set email alerts
|

The G8 screening tool enhances prognostic value to ECOG performance status in elderly cancer patients: A retrospective, single institutional study

Abstract: BackgroundSome elderly cancer patients, even with good Eastern Cooperative Oncology Group performance status (ECOG-PS), have poor survival outcomes and cannot tolerate standard therapy. Few studies have detailed the associations between the G8 screening tool, ECOG-PS, and overall survival (OS) in such patients.MethodsCancer patients, aged 70 years or older, were assessed for G8 and classified into three groups according to their G8 score: <11 as the low score group, 11–14 as the intermediate score group, and >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 32 publications
(59 reference statements)
4
50
1
4
Order By: Relevance
“…In a previous retrospective study, Takahashi et al showed that the G8 screening tool adds prognostic value to ECOG-PS in older patient with cancer, with classification into three groups according to two G8 score cut-off values [20]. Other studies also used two cut-offs to improve identification of at-risk patients [15,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous retrospective study, Takahashi et al showed that the G8 screening tool adds prognostic value to ECOG-PS in older patient with cancer, with classification into three groups according to two G8 score cut-off values [20]. Other studies also used two cut-offs to improve identification of at-risk patients [15,22].…”
Section: Discussionmentioning
confidence: 99%
“…Total scores range from 0 to 17, with a score ≥ 14 defined as normal and a score b 14 defined as abnormal (according to the conventional classification system) [13]. For more efficient identification of patients with a poor prognosis, they were also divided into three groups by G8 score: 14.5-17, high score group; 10.5-14, intermediate score group; and b10.5, low score group [20].…”
Section: G8 Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is plausible that subjects with more advanced cancer, and particularly with gastrointestinal and head/neck tumour are frequently comorbid for malnutrition [ 22 ], due to the intense inflammatory response associated with anorexia and cachexia [ 23 ], which can lead to progressive loss of skeletal muscle mass and worsen impairment of function [ 24 ]. Malnutrition has been associated with reduced ability to tolerate anti-cancer therapy, increased severe dose-limiting toxicities, lesser response rates, worse quality of life, decline in performance status, and shorter survival outcomes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frailty was determined by a least one positive criteria on Fried frailty [22,23] or by a Geriatric-8 (G8) score < 14 [24]. Discharge was managed through standardized discharge criteria.…”
Section: Other Variablesmentioning
confidence: 99%